Pendampingan Pembuatan Nomor Induk Berusaha (NIB) Guna Mengoptimalisasi Legalitas UMKM di Kelurahan Kutisari - Ramadani, Nifta Dwi; Yuniningsih, Yuniningsih (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Assistance in making the Business Identification Number (NIB) aims to optimize the legality of Micro, Small, and Medium Enterprises (MSMEs) in the Kutisari Village, Tenggilis Mejoyo District, Surabaya City. MSMEs are an economic sector consisting of businesses with relatively limited operational scale and capital. Businesses that are established and operating in Indonesia should have legal status as an official identity, which will be very useful in the development and empowerment of the business. Assistance in making the NIB is carried out directly and centrally through the Online Single Submission (OSS) website. The methods used in this activity include collecting and processing data of MSME actors, coordinating with stakeholders in Kutisari Village, preparing assistance activities, implementing assistance activities, and handing over legal documents in the form of NIB. Assistance in making the NIB has successfully optimized the legality of MSMEs in Kutisari Village, with a significant increase of 67 registered MSMEs. With this official identity, it is hoped that MSMEs can more easily access various support and develop their business potential sustainably.